Fuel Cell: A Review and a New Approach About YSZ Solid Oxide Electrolyte Deposition Direct on LSM Porous Substrate by Spray Pyrolysis - Falcade, Tiago; Malfatti, Célia de Fraga (IntechOpen, 2012)
None